Вы находитесь на странице: 1из 2

A)

x2y2 + 2xy = x
y(x) = (-2xy2 2y + 1)
2x (xy + 1)
B)
ysen x + y= 3y
x
y(x) = y x2 y cos(x)___
x(-3x + x sin(x) + 1
c)
ytan x + xcos y = 1
y(x) = sec2(x) + cos(y)
x sin(y) tan(x)
d)
__xy__ = 1/x
x2-y2

2x2y_ _ _ y _ _ _1_
__(x2-y2)2
x2-y2
x2__
2xy2 + __ x__
(x2-y2)2
x2-y2

Y(x) =

e)
x+y + x = 2x2y2
x-y

y(x) =

4xy2 + x+y _ __1__ _ 1


_______ (x-y)2
(x-y)_______
2
- 4x y + x+y + 1
(x-y)2
(x-y)

f)
senx = 3ycosy
y
y(x) =

_ ___________ycos(x)___________
- sen(x) + 3y3 sen(y) 3y2 cos(y)

g)
ey cos x e(ysenx) = ln xy

y(x) =

y(xy cos(x) eysin(x) + 1)


x(-y sin(x) eysin(x) ey) y- 1